Ceo Competency And Earnings Management: Evidence From Nigerian Financial Firms - Usaini, Muhammad (2023)
This study examined the influence of corporate governance (CG) mechanism (board size, board independence, CEO duality and audit committee) on earnings management (EM) of financial listed firms. It also investigated the moderating role of CEO competency on the relationship between corporate governance and earnings management. Using a sample of deposit money banks, mortgage banks and insurance firms in Nigeria, the study adopted the panel regression estimator to analyze the testable hypotheses. In support of the agency theory, the study found evidence that there is a partial support for the influence of corporate governance mechanisms on earnings management because only audit committee was found to have a significant impact on earnings management. Earnings management can also be minimized through CEO competency. In addition, the study found that CEO competency significantly moderates the relationship between audit committee and earnings management while there is no support for the moderating role of CEO competency on the relationship between board size, board independence, CEO duality, and earnings management.